The Impact of Digital Transformation and Remote Work on Performance Appraisal of The Business Service in Indonesia Following the Pandemic - Permata Veithzal, Andria (Dinasti Publisher, 2023)
The aim of this study is to investigate the correlation between digital transformation, remote work, motivation, and performance appraisal in the service industry of Indonesia following the COVID-19 pandemic. The present investigation utilizes quantitative techniques, more precisely descriptive approaches. The present study employs a sample of 133 participants to investigate the performance of service businesses. The current investigation utilizes the SPSS 26 software to conduct data analysis.